High‐flux and solvent‐selective membranes with aromatic functionalities and dual‐layer structures. Issue 1 (16th July 2021) - Hao, Lan; Cui, Xulin; Wu, Xiaoli; Wang, Jingtao; Li, Yifan; Li, Wenpeng; Cao, Xingzhong; Zhang, Haoqin
Abstract: Efficient separation of aromatic‐aliphatic hydrocarbon mixtures has long been an important topic in chemical industries. Organic nanofiltration (OSN) has been revealing great promise in separating solvent mixtures that has not been effectively resolved by the state‐of‐the‐art technologies. Herein, novel OSN membranes are designed for the separation of toluene and n ‐heptane. Polyamide active layer with diaminonaphthalene as the aqueous phase monomer is prepared by interfacial polymerization for the first time. The addition of polydimethylsiloxane gutter layer, as well as the combination of spin coating technique and macroporous substrate, renders the membranes with loose and defect‐free architectures. The as‐designed membranes achieve a rather high selectivity of toluene over n ‐heptane (>4) together with ultra‐high toluene permeance (>180 L m −2  h −1  bar −1 ). These membranes also present excellent stability in the long‐term operation. Abstract :